2013
DOI: 10.1177/0141076812472617
|View full text |Cite
|
Sign up to set email alerts
|

Geographical movement of doctors from education to training and eventual career post: UK cohort studies

Abstract: Many doctors do not change geographical region in their successive career moves, and recent cohorts appear less inclined to do so.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…The importance of locality in terms of training near friends and family is of interest. Many studies have shown that medical graduates typical migrate back home at some point in their careers 64‐66 . Our definition of location, developed via qualitative work, 7 specifically included reference to being near family and friends who are important in terms of social support.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of locality in terms of training near friends and family is of interest. Many studies have shown that medical graduates typical migrate back home at some point in their careers 64‐66 . Our definition of location, developed via qualitative work, 7 specifically included reference to being near family and friends who are important in terms of social support.…”
Section: Discussionmentioning
confidence: 99%
“…Research has examined how factors such as geographical location, gender, career aspiration, work-life balance and perceived financial rewards play a crucial role in determining the career choice of healthcare workforce 9–15. Other studies have looked at the relationship between socioeconomic origin and where doctors practice 16 17.…”
Section: Introductionmentioning
confidence: 99%
“… 30 Related to this, London and the South of England are where much of the UK population is based, and many medical students and early career doctors prefer to train and work nearby their family and friends. 31 32 Finally, applicants from areas of high educational participation and from independent schools—and note there is a strong relationship between these two factors 33 34— may be more likely to apply to highly competitive foundation schools (eg, London and the South of England). Taking these factors as a whole, London and the South of England are very popular places to train and work, and so there is more competition for places.…”
Section: Discussionmentioning
confidence: 99%